CHARACTERS OF MINANGKABAU PEOPLE THROUGH EXPRESSION AS SEEN ON POLITICAL ASPECTS: KARAKTER ORANG MINANGKABAU MELALUI UNGKAPAN DITINJAU DARI ASPEK POLITIK - M Sayuti; Ali Mardius; Efrianto Efrianto (LLDIKTI Wilayah X, 2022)
This study aims to describe the character of the Minangkabau community through their expressions reviewed from the political aspect. This is a descriptive qualitative research, sample of 60 people are randomly assigned to represent traditional stakeholders. The research instrument is a questionnaire. The informen came from the core area of Minangkabau. It was found that the character of the Minangkabau people was based on two systems; the Koto Piliang harmony system pioneered by Datuk Ketumanggungan and the Bodi Caniago harmony system was pioneered by Datuk Perpatih Nan Sabatang political system emanates from the earth. These opposing systems produce two systems based on: democracy, egalitarianism, and social justice aspects. In political democracy, Minangkabau people making decisions through deliberation to reach consensus, which is expressed by